2019
DOI: 10.20944/preprints201907.0009.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic Crack Detection of Road Pavement Based on Aerial UAV Imagery

Abstract: Road surface monitoring more specifically crack detection on the surface of the road pavement is a complicated task which is found vital due to critical nature of roads as elements of transportation infrastructure. Cracks on the road pavement is detectable using remotely sensed imagery or car mounted platforms. UAV’s are also considered as useful tools for acquiring reliable information about the pavement of the road. In This paper, an automatic method for crack detection on the road pavement is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Automatic crack detection of road pavement based on aerial UAV imagery [75] SVM, edge-based approach This work proposes a programmed technique for crack recognition out and about asphalt using procured recordings from the UAV stage.…”
Section: Cnnmentioning
confidence: 99%
“…Automatic crack detection of road pavement based on aerial UAV imagery [75] SVM, edge-based approach This work proposes a programmed technique for crack recognition out and about asphalt using procured recordings from the UAV stage.…”
Section: Cnnmentioning
confidence: 99%
“…The timely and proper maintenance of forest roads is essential for sustainable serviceability of roads, and an effective method to detect road surface problems is Unmanned Aerial Vehicles (UAV) (Tan and Li 2019). UAV's are considered useful tools for acquiring reliable information about the surface of the forest road (Dadrasjavan et al 2019). Ruzgienė et al (2015) showed that the correctness of the digital surface model for roads generally depends on camera resolution, ight height, and accuracy of ground control points.…”
Section: )mentioning
confidence: 99%
“…6a) were automatically subjected to a pre-processing and enhancement process (Sobel operator and Prewit), then they were segmented (edge detector, Canny filter, Gaussian filter) and classified (Support Vector Machine) to be able to extrapolate the information we need (Fig. 6b) (Grüen & Li, 1997;Serna & Marcotegui, 2014;Ameri, Dadrass Javan, & Zarrinpanjeh, 2019;Dadrasjavan, Zarrinpanjeh, & Ameri, 2019). In particular, the SVM classification was carried out in two phases:…”
Section: Image Acquisition and Processingmentioning
confidence: 99%